The effect of an acute bout of rugby training on plasma concentrations of intestinal fatty acid binding protein - Chantler, S.; Jones, B.; Roe, G.; Phibbs, P.; Owen, C.; Griffiths, A.; Ramirez-Lopez, C.; Davison, G.; Deighton, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Exercise appears to elicit damage to the gut endothelial cell lining, as demonstrated by elevated plasma concentrations of intestinal fatty acid binding protein (iFABP). However, the majority of research to date has focussed on responses to endurance exercise, with little understanding of the potential impact of contact-based sports on gastrointestinal damage. The high intensity nature of rugby, combined with trauma from collisions, suggests that this may cause considerable increases in gastrointestinal damage and permeability. The aim of this study was to investigate the effects of a standardised rugby training session on plasma concentrations of iFABP as a marker of gastrointestinal damage.